The cytoplasmic region of the erythropoietin receptor contains nonoverlapping positive and negative growth-regulatory domains. - D'Andrea, A D (1991)
The erythropoietin (EPO) receptor (EPO-R), a member of a large cytokine receptor superfamily, has a 236-amino-acid cytoplasmic region which contains no obvious tyrosine kinase or other catalytic domain. In order to delineate the linear functional domains of the cytoplasmic tail, we generated truncated mutant cDNAs which were transfected into a murine interleukin-3-dependent cell line, Ba/F3, and the EPO-dependent growth characteristics of the stable transfectants were assayed. We identified two unique domains of the cytoplasmic tail. A membrane-proximal positive signal transduction domain of less than or equal to 103 amino acids, in a region highly similar to the interleukin-2 receptor beta chain, was sufficient for EPO-mediated signal transduction. A carboxy-terminal negative-control domain, a serine-rich region of approximately 40 amino acids, increased the EPO requirement for the Ba/F3 transfectants without altering EPO-R cell surface expression, affinity for EPO, receptor oligosaccharide processing, or receptor endocytosis. Truncation of this negative-control domain allowed the Ba/F3 transfectants to grow maximally in only 1 pM EPO, 1/10 the concentration required for growth of cells expressing the wild-type EPO-R. All truncated EPO-R mutants which retained the transmembrane region of the EPO-R polypeptide bound to the gp55 envelope protein of Friend spleen focus-forming virus. Only the functional EPO-R mutants were activated by the gp55, however, suggesting that gp55- and EPO-mediated signaling occur via a similar mechanism.